1994
DOI: 10.1086/173541
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of one-point distributions from Gaussian initial fluctuations

Abstract: We study the quasilinear evolution of the one-point probability density functions (PDFs) of the smoothed density and velocity fields in a cosmological gravitating system beginning with Gaussian initial fluctuations. Our analytic results are based on the Zel'dovich approximation and laminar flow. A numerical analysis extends the results into the multistreaming regime using the smoothed fields of a CDM N-body simulation. We find that the PDF of velocity, both Lagrangian and Eulerian, remains Gaussian under the l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
250
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 170 publications
(273 citation statements)
references
References 32 publications
22
250
1
Order By: Relevance
“…The assumed Gaussianity of the velocity Ðeld in the mildly nonlinear regime is supported by simulations (Kofman et al 1994 ;Kudlicki et al 2001) and is veriÐed by the nearly normal distribution of the observed ln (z/d) in our sample.…”
Section: Ikelihood Analysissupporting
confidence: 74%
“…The assumed Gaussianity of the velocity Ðeld in the mildly nonlinear regime is supported by simulations (Kofman et al 1994 ;Kudlicki et al 2001) and is veriÐed by the nearly normal distribution of the observed ln (z/d) in our sample.…”
Section: Ikelihood Analysissupporting
confidence: 74%
“…Coles & Jones (1991) suggested to describe the three-dimensional matter density distribution in our Universe by a log-normal random field. Later, numerical simulations of cosmic structure formation showed that a log-normal field provides indeed a good description of the one-and two-point statistics of the evolved matter density field, even though a point-wise exponential mapping of the initial Gaussian density field does not describe the evolved density field well (Kofman et al 1994;Kayo et al 2001). The one-point probability density function (pdf) of the projected density and lensing convergence are also fitted well by a log-normal pdf (Taruya et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…For each model we will analyse the velocity field defined on a 128 3 mesh. The field is obtained using the same procedure as in Kofman et al (1994). First we interpolated mass and momentum from the particle distribution on a regular cubic grid by means of a Triangular Shaped Cloud (TSC) scheme (see Hockney & Eastwood 1981).…”
Section: General Properties Of Velocity Fieldsmentioning
confidence: 99%
“…Gelb & Bertschinger 1994) and is unable to reproduce the slope of the galaxy angular correlation function obtained from the APM survey (Maddox et al 1990).…”
Section: Introductionmentioning
confidence: 98%